Designing research in the social sciences - Maggetti, Martino (SAGE, 2013)
This innovative research design text will help you make informed choices when carrying out your research project. Covering both qualitative and quantitative approaches, and with examples drawn from a wide range of social science disciplines, the authors explain what is at stake when choosing a research design, and discuss the trade-offs that researchers have to make when considering issues such as causality, categories and classification, meaning, levels of analysis, and time.